S-210JA-29 ゴウキ ニヨル デンリケン プラズマ ノ カンソク ケッカ f. キョクイキ デンリソウ ダイ2カイ キョクイキ ニオケル デンリケン ジキケン ソウゴウ カンソク シンポジウム PART 2 - 宮崎, 茂; ミヤザキ, シゲル; 森, 弘隆; モリ, ヒロタカ; 小川, 忠彦; オガワ, タダヒコ; MIYAZAKI, Shigeru; MORI, Hirotaka; OGAWA, Tadahiko (1980)
P(論文) S-210JA-29号機は第18次南極地域観測隊によって,1977年7月12日19時15分(LT)に発射された.電子密度高度分布は85-115kmのE_s層の存在を示し,その密度は2-4×10^4/cm^3である.D領域(70km以下)のenhancementはなく,また115km以上の高さでは,密度の著しい単調減少を示している.このプロファイルは,今までの夜間の測定結果と比較すると,かなり低い密度を示していることが注目される.この時のリオメータ,イオノグラムおよびマグネトグラムの記録は静穏であることを示している.また観測された静電ノイズのスペクトルは,高度に対してきわめて著しい変化を示している.上昇時高度95-106km,下降時103-112kmにおいて,ゆらぎの振幅が大きくなり,1-2kHzにピークをもち,スペクトルは高周波側へ伸びているのが観測された.今回観測されたノイズが自然のものであるとすると,スペクトルの数kHz帯の成分は,2流体プラズマ不安定性によるイオン波の可能性を示唆する. In order to measure the electron density and density irregularities in the polar ionosphere sounding rocket S-210JA-29 was fired at 19h15m (LT) on July 12, 1977 from Syowa Station, Antarctica. The observational results show that there exists an E_s layer in the altitude region between 85 km and 115 km, and its electron density is 2-4×10^4/cm^3, and the electron density above 115 km is decreasing. The values of the measured electron density profile are rather low compared with the nighttime electron density profiles which were observed until now. The profiles of the electrostatic noise spectrum show remarkable changes against the altitude. The amolitudes of spectrum of the electrostatic noise become great in the region between 95 km and 106 km in the ascending time and between 103 km and 112 km in the descending time. The amplitudes of spectrum have a peak value at 1-2 kHz and the spectrum spreads out to the higher frequency region. Assuming that the observed spectrum of the electrostatic noise to be a natural one, these irregularities seem to be caused partly by a two-stream plasma instability mechanism. departmental bulletin paper